1971
DOI: 10.1111/j.1467-6494.1971.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal‐external locus of control and response to influence attempts1

Abstract: Summary It was hypothesized that subjects having external locus of control orientations (E's) would conform to both subtle and overt influence attempts, whereas internals (I's) would react against such attempts 144 undergraduate students (72 of each sex) rated a proposed grading procedure pre‐ and postinfluence Data were analyzed in a completely crossed and balanced 3‐way factorial design, which included 3 levels of locus of control (I's, middles, and E's), 3 levels of influence (no, low, and high), and 2 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
3

Year Published

1974
1974
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 10 publications
2
38
0
3
Order By: Relevance
“…The structure of locus of control is based on a general belief difference between individuals having internal and external locus of control. While individuals with an internal locus of control believe that their achievements or their destiny is under their control, individuals with an external locus of control link their achievements and their destiny with external factors (Biondo & Macdonald, 1971;Pines & Julian, 1972;Mitchell, Smyser, & Weed, 1975;Zuckerman & Gerbasi, 1977;Marsh & Richards, 1987;Boone, Brabander, & Witteloostuijn, 1996). Individuals with internal locus of control possess a great ability to dominate and affect people around them (Pandey & Tewary, 1979).…”
Section: Personal Backgroundmentioning
confidence: 99%
“…The structure of locus of control is based on a general belief difference between individuals having internal and external locus of control. While individuals with an internal locus of control believe that their achievements or their destiny is under their control, individuals with an external locus of control link their achievements and their destiny with external factors (Biondo & Macdonald, 1971;Pines & Julian, 1972;Mitchell, Smyser, & Weed, 1975;Zuckerman & Gerbasi, 1977;Marsh & Richards, 1987;Boone, Brabander, & Witteloostuijn, 1996). Individuals with internal locus of control possess a great ability to dominate and affect people around them (Pandey & Tewary, 1979).…”
Section: Personal Backgroundmentioning
confidence: 99%
“…This might especially be the case for people who do not believe that they are in control over their life's events (e.g., externals). We expected differential effects between externals and internals for this type of social situation because of the large number of prior studies on LOC which shows that externals are more sensitive to social processes than are internals (Davis and Phares, 1967;Pines and Julian, 1972;Biondo and MacDonald, 1971). Consequently we expected to see greater effects of control encouragement in externals than in internals in this study.…”
mentioning
confidence: 95%
“…These attitudes are somewhat difficult to characterize according to the LOG dimension. Much of the research literature shows that internals resist social influence to a greater degree than do externals (Biondo & MacDonald, 1971 ;Cravens & Worchel, 1977). On the other hand, Mc~ollaum and Lester (1995) found that an antiauthority orientation was associated with externality on the Rotter LOG scale.…”
Section: Macho and Resignationmentioning
confidence: 99%